PENERAPAN KONSEP LEAN MANUFACTURING UNTUK MENINGKATKAN KAPASITAS PRODUKSI (STUDI KASUS : LANTAI PRODUKSI PT.TATA BROS SEJAHTERA) - Sumiharni Batubara; Fidiarti Kudsiah (JURNAL TEKNIK INDUSTRI, 2012)
Lean Manufacturing is an approach to increase the efficiency of a system through a continuous improvement to minimize waste. This approach begins by creating a value stream mapping, an overview of an organization through information/activity flow and material flow that takes place at the shop floor. These activities are then classified as value-added activities and non-value added activities. The complication arises when production target cannot be met, delaying product delivery to consumers. This delay, mainly driven by lengthy production time, is typically caused by waste that occurs at the shop floor. By identifying the source of those wastes, production time can be reduced to fulfill production target. This paper utilized the lean manufacturing approach as an initial step to perform standard time calculation for all activities that eventually were identified as Value-added or Non Value-added Current State Activity. Further, to obtain the complete picture of the shop floor, value stream mapping were performed and Process Cycle Efficiency was calculated. Waste, defined as transportation time required for semi-finished products from one process to the next and any unnecessary motions within some process, were then identified. To minimize transportation time, transfer batch was utilized. While to decrease operation time, motion improvements were done through Right Hand – Left Hand Process Chart. Upon improvement, manufacturing lead time decreased by 4.7% and Process Cycle Efficiency increased by 2%.